2019
DOI: 10.14740/jocmr3724
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbilirubinemia as a Predictor of Appendiceal Perforation: A Systematic Review and Diagnostic Test Meta-Analysis

Abstract: Background Misdiagnosis of the severity of acute appendicitis may lead to perforation and can consequently result in increased morbidity and mortality. In this study, the role of hyperbilirubinemia as a predictor of perforation is assessed by performing a meta-analysis of diagnostic accuracy. Methods A systematic search of the literature published over the past 20 years was performed using the EMBASE, PubMed, Cochrane library, and Google Scholar databases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 29 publications
3
14
0
Order By: Relevance
“…They described the rate of appendicular perforation as being 3 times higher for patients with hyperbilirubinemia compared to normal bilirubin levels. Diagnostic accuracy of hyperbilirubinemia in predicting perforated appendicitis was demostrated by several clinical studie [15][16][17][18][19]. More important, in the present study, hyperbilirubinemia proved to be an important biomarker for intraperitoneal sepsis diagnosis and monitoring.…”
Section: Bilirubin (C33h36n4o6)supporting
confidence: 55%
“…They described the rate of appendicular perforation as being 3 times higher for patients with hyperbilirubinemia compared to normal bilirubin levels. Diagnostic accuracy of hyperbilirubinemia in predicting perforated appendicitis was demostrated by several clinical studie [15][16][17][18][19]. More important, in the present study, hyperbilirubinemia proved to be an important biomarker for intraperitoneal sepsis diagnosis and monitoring.…”
Section: Bilirubin (C33h36n4o6)supporting
confidence: 55%
“…Biomarkers have the potential to provide noninvasive objective criteria without any adverse effects on the patient [ 13 ]. Serum bilirubin has been suggested as a possible marker of perforation, as hyperbilirubinemia commonly occurs in patients with septic conditions [ 14 , 15 ]. Bacteremia can cause endotoxemia leading to impaired excretion of bilirubin from the bile canaliculi [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, hyperbilirubinemia alone has a low overall accuracy to diagnose a complicated appendicitis with anticipated perforation. In cases where elevated bilirubin occurs, the patient is more likely to be diagnosed with complicated appendicitis [ 14 ], and normal bilirubin supports the presence of an uncomplicated appendicitis [ 15 ]. More research is needed to evaluate whether measurement of serum bilirubin should be integrated into the diagnostic tools when it comes to appendicitis.…”
Section: Resultsmentioning
confidence: 99%
“…All of these scores have been proven useful in predicting AA, but none of them evaluate the risk of perforation. [5] USG and CT are the most preferred imaging modalities. In a meta-analysis, Al-Khayal et al [12] stated that USG had a sensitivity of 83.7% and specificity of 95.9% in cases suspected to have AA.…”
Section: Discussionmentioning
confidence: 99%
“…However, these two techniques have a low sensitivity in detecting perforated AA. [5] On the other hand, despite the higher specificity and sensitivity values, the downside of CT is exposure to ionized radiation. In a study by Smith-Bindman et al, [14] it was demonstrated that there was an increase in the rate of cancer associated with CTrelated radiation, particularly among young people.…”
Section: Discussionmentioning
confidence: 99%